Analisis Indikator Pelayanan Rawat Inap Kasus Covid-19 di RSUD Harapan dan Doa Kota Bengkulu Tahun 2021 - Nofri Heltiani; Ismail Arifin; Joko Purnomo (Iris Journal of Health Information Management, 2022)
The importance of calculating inpatient indicators as information on RL1 data which is the hospital's basic data. Based on the results of interviews with IRNA Isolation Covid-19 officers during the pandemic, the implementation of SHRI did not run so that the calculation of the BOR, AvLOS, TOI, BTO, GDR and NDR indicator values was not carried out because the SHRI data was not obtained and processed to determine the value of inpatient service indicators. The impact of not doing it on the manufacture of RL1 which is not precise and accurate so that it does not produce up-to-date data. This study aims to determine the indicators of inpatient services for COVID-19 cases for the period January to August at Harapan and Doa Hospitals, Bengkulu City in 2021. This type of research is descriptive with a cross sectional approach. The population and sample in this study were data on visits to COVID-19 patients for the period January to August 2021 as many as 965 patients, the total population sampling technique. The data used in this study is secondary which is processed and analyzed univariately using the formula for inpatient indicators. The results obtained from the calculation of values for the period January to August 2021 are BOR 34.92 (not ideal), AvLOS 5.22 (not ideal), TOI 9.92 (not ideal), BTO 15.93 (not ideal), GDR 64.86 (not ideal) and NDR 23.01 (ideal). The indicator values for inpatient services for Covid-19 cases for the period January to August 2021, namely BOR, AvLOS, TOI, BTO, GDR have not been efficient, but the NDR value is efficient. Hospitals should improve medical services for Covid-19 patients and increase efficiency and effectiveness as consideration for decision-making and planning strategies for the following year in the service of Covid-19 patients.